M1/M2 macrophage polarization in human obese adipose tissue - Chylikova, Jaroslava; Dvorackova, Jana; Tauber, Zdenek; Kamarad, Vojtech (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
Obesity and insulin resistance are closely associated with chronic inflammation in adipose tissue, where macrophages play an important role. Adipose tissue macrophages can be divided into two main phenotypes: the classical M1 macrophages and alternatively activated macrophages M2. M1 macrophages produce pro-inflammatory cytokines (TNF-α, interleukin IL-6 and MCP-1) and thus contribute to the development of insulin resistance. On the other hand, M2 macrophages, anti-inflammatory, are involved in the maintenance of tissue homeostasis and are typical in the adipose tissue of slender individuals. Macrophages can also play a role in the pathogenesis of other serious illnesses such as cardiovascular diseases or cancer. This article reviews the latest data on macrophage polarization in adipose tissue.
Keywords: Insulin Resistance; fenotyp; Phenotype; inzulinová rezistence; adipose tissue; obesity; Obesity; Tumor Necrosis Factor-alpha; Chemokine CCL2; chemokines; tuková tkáň; chemokin CCL2; Hypoxia; Interleukin-6; obezita; M1/M2 macrophages; lidé; Adipose Tissue; interleukin-6; Humans; makrofágy; inflammation; TNF-alfa; Macrophages; hypoxie